Effects of cognitive training under hypoxia on cognitive proficiency and neuroplasticity in remitted patients with mood disorders and healthy individuals: ALTIBRAIN study protocol for a randomized controlled trial - Woznica Miskowiak, Kamilla; Damgaard, Viktoria; Schandorff, Johanna Mariegaard; Macoveanu, Julian; Knudsen, Gitte Moos; Johansen, Annette; Plaven-Sigray, Pontus; Svarer, Claus; Fussing, Caroline Bruun; Cramer, Katrine; Jørgensen, Martin Balslev; Kessing, Lars Vedel; et al. (Trials, 2024)
Cognitive impairment is prevalent across neuropsychiatric disorders but there is a lack of treatment strategies with robust, enduring effects. Emerging evidence indicates that altitude-like hypoxia cognition training may induce long-lasting neuroplasticity and improve cognition. We will investigate whether repeated cognition training under normobaric hypoxia can improve cognitive functions in healthy individuals and patients with affective disorders and the neurobiological underpinnings of such effects.
Gesehen am 29.04.2025